eMMI (e-MODULE MULTIPLE INTELLIGENCE) : MODUL FISIKA DASAR MAHASISWA DENGAN 3D PAGEFLIP PRO - Khoirun Nisa; Ismi Nurul; Mistianah Mistianah (Universitas Tribhuwana Tunggadewi, 2021)
This study aims to produced eMMI based on multiple intelligence (eMMI) with 3D pageflip pro for biology student’s in IKIP Budi Utomo Malang, in the circulatory system material that is suitable for used in the learning process. This research was developed with a 4-D model consisting of definitions, planning, development and dissemination. Data collection using a questionnaire. This eMMI have been validated by material experts and media experts.The evaluation results from material validation, is known that above 90%, while the results of media validation are above 96%. Small scale test results indicate the validity results above 90%. From the results of the validation of media experts and material experts, it is stated that the e-eMMIe is suitable for use and based on the questionnaire, it can be said that students and teachers are expected to really take advantage of teaching materials in order to create interesting and fun learning in physics learning.